Vacancy-ordered yttria stabilized zirconia as a low-temperature electronic conductor achieved by laser melting. Issue 4 (April 2019) - Song, Lu; Zhang, Qinghua; Ma, Jing; Chen, Chonglin; Xu, Ben; Zhu, Mingke; Xu, Xing; Nan, Cewen; Shen, Zhijian
Graphical abstract: Abstract: Laser melting is known to be capable in initiating thorough evolution in microstructure and bringing novel functional performance in metals. But realization of this potential in ceramics only reaches a preliminary stage that needs further investigation. Here we demonstrate zirconia, traditionally an insulative ceramic at low temperature, could be transformed into an electronic conductor with the conductivity on order of 10 −3 S⋅cm -1 at room temperature by a simple laser melting process without inducing metallic phases. Transmission electron microscopy and ab-initio simulation show that oversaturated oxygen vacancies, together with their ordered metastable distribution along <001 > , are introduced during this non-equilibrium process, and result in a clear defect level significantly narrowing bandgap to less than 1 eV, leading to the considerable electronic conductivity. These results identify a strategy of utilizing this non-equilibrium method in oxide ceramics to realize some unconventional performances determined by metastable structure thoroughly altered down to atomic level.